Penyuluhan Pembuatan MoL Bonggol Pisang Berbasis Tingkat Adopsi dan Faktor-Faktor Mempengaruhi di Gapoktan Tani Makmur - Kusumaningrum, Faridha Diyana; Windari, Wahyu; Riyanto, R (Journal Galung Tropika, 2020)
Gapoktan Tani Makmur is an association of farmer groups in Kartoharjo Village. The main product of Gapoktan is semi-organic fertilizer, namely organic NPK super granule with the trademark was ASLI (Alami Subur Lestari Indonesia). The problem faced is that Gapoktan is very dependent on factory microbes that were no longer produced in Purbalingga. There are many potential sources of beneficial local microorganisms, one of which comes from banana weevils. The purpose of this study was to describe the level of adoption and to analyze the factors that influence the adoption rate as the basis for the design of education about the manufacture of banana weevil MOL in Gapoktan Tani Makmur. Also, to determine the implementation, evaluate education based on the level of adoption and the factors that influence it. The method used is a quantitative approach with a survey method for data collection. The sampling technique uses random cluster sampling. The results showed that the measurement of the adoption rate before counseling was in the very high category of 82.9%, with the regression line equation Y = -2.695 + 0.124X1 - 0.558X2 + 2.182X3 + 1.958X4, with a determination coefficient of 0.829 or 82.9% . It means that the variable age (X1), an education level (X2), attitude towards change (X2), and courage at risk (X2) simultaneously affect the innovation adoption variable (Y) by 82.9%. Simultaneously, the rest is influenced by other variables or variables not studied. The extension's design follows the measurement of adoption rate and its influencing factors. The extension material includes the meaning, benefits, advantages, and MOL content of banana weevils for super organic NPK fertilizer. Real-life media outreach, PPT slides, and leaflets with adjuncts, lectures, and demonstrations. Evaluation of the extension design application, namely, evaluating the adoption rate of 38 target people with a very high category of 86.4%.